Defining the Study of Humanistic Personality Psychology of the Main Character of the Novel Si Anak Pelangi by Tere Liye: The Value of Character Education and Its Relevance to Learning - Muhammad Agus Tri Wibowo; Slamet Subiyantoro; Kartika Chrysti Suryandari (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to examine the psychological aspects of the main character in the novel “Si Anak Pelangi” by Tere Liye. Moreover, this study also investigates the value of character education and its relevance to learning Indonesian in elementary school. The research method uses a descriptive qualitative approach. The data was the document of the novel which was analyzed using content analysis method. The results of this study are related to the Haberman's humanistic psychological theory, namely (1) technical learning, (2) practical learning, and (3) emancipatory learning. In addition, there are several values of character education such as (1) hard work in the form of doing activities diligently and accompanied by sincere intentions, (2) politeness in speech and behavior, (3) giving awards by sincerely accepting someone's gift, (4 ) positive, in acting both in sports and interacting with others, and (5) being patient in dealing with insults. This study concludes that this novel has suitable content for elementary school students since it contains positive values and educating characters.